An Explanatory Study: Exploring EFL Students’ Attitudes Toward the Use of AI Tools in Academic Writing - Hidayat, Nur (ELLITE: Journal of English Language, Literature, and Teaching, 2025)
The purpose of this study was to investigate EFL learners' attitudes on the use of AI-powered tools in academic writing with the challenges. Combining quantitative and qualitative research, this mixed-methods study followed an explanatory study design. The researcher gathered the data through questionnaires and semi-structured interviews. Using SPSS through descriptive statistics analysis preceded by validity and reliability tests of the research instrument, researchers analyzed quantitative data. The thematic analysis helped the researcher to examine qualitative data. Triangulation was also done to validate the findings from the qualitative and quantitative data. The results of this study showed that EFL students had a positive attitude toward the application of artificial intelligence in academic writing, including encompassing structuring ideas, enhancing sentence structure, and raising self-confidence. However, the overuse of artificial intelligence shows signs of caution, such as a decline in its inventiveness and critical thinking. Besides, using artificial intelligence in academic writing presents some challenges for learners. These challenges include the quality of arguments and the validity of references presented by the AI as well as the detection of AI generated.